The effect of capital structure on a firm's liquidation decision - Titman, Sheridan (Journal of Financial Economics, 1984)
A firm's liquidation can impose costs on its customers, workers, and suppliers. An agency relationship between these individuals and the firm exists in that the liquidation decision controlled by the firm (as the agent) affects other individuals (the customers, workers, and suppliers as principals). The analysis in this paper suggests that capital structure can control the incentive/conflict problem of this relationship by serving as a pre-positioning or bonding mechanism. Appropriate selection of capital structure assures that incentives are aligned so that the firm implements the ex-ante value-maximizing liquidation policy.